Korelasi Perilaku Struktur Bangunan Berdasarkan Parameter R, Cd dan Ω Terhadap Tingkat Kinerja pada Beragam Simulasi Gempa - Nurhidayatullah, Eka Faisal; Kurniati, Dwi; Maradika, Samsul Ryandi (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
This research was conducted by modeling the reinforced concrete structure according to the existing conditions. Nonlinear static pushover analysis was carried out by giving monotonous lateral static loads until the structure reached an inelastic nonlinear state which was known from its capacity curve. The frequent, rare and very rare earthquake scenarios are given to the building structure so that the level of performance is known. The performance of the simulated building for each earthquake level is correlated with the parameters R, Cd and Ω of the actual building structure. The parameter values of Ractual, Ωactual and Cdaktual represent the strength, stiffness and ductility of building structure are in good condition. The degradation of stiffness and strength due to an increase of base shear occurs faster when the earthquake acts at Y than X direction of building. Small, design and large earthquake simulations show immediate occupancy buildings’ performance level so that the structure is included in very good category. The presence of shear walls on all four sides of the building is suspected as the cause. Improving the quality of building structure performance can be done by modifying the structural parameters R, Cd and Ω. In existing buildings, can be done by retrofitting, adding shear walls, braces or passive control devices neither seismic dampers nor base isolation.